EFFECTIVENESS OF HIGH SCHOOL GIRLS LACROSSE HEADGEAR MANDATE IN THE REDUCTION OF HEAD AND FACE INJURIES. Issue 3 (31st March 2019) - Veasley, Shayla; Baron, Samuel L.; Nguyen, Michael; Anil, Utkarsh; Alaia, Michael; Cardone, Dennis; Testa, Noel
INTRODUCTION: Due to a large number of eye injuries in girls' lacrosse, US Lacrosse instituted a rule making protective eye-wear mandatory starting in the 2004-2005 season. Although the eye-wear was shown to significantly reduce injuries to the eyes, injuries to the head and face are still commonly reported despite body checks and stick checks to the body being illegal. In 2016, US lacrosse ruled that headgear could be used by its teams as long as it meets ASTM standard F3137*. There has been continued controversy over whether or not headgear in women's lacrosse could make players more aggressive and/or lead to fewer dangerous call penalties by the officials, thus increasing the head and face injury rate. In 2017, the Public Schools Athletic League, which governs most scholastic sports in New York City, became the first high school organization in the country to mandate ASTM standard F3137 headgear for all women's lacrosse players. The purpose of this study is to investigate the effect of ASTM standard F3137 approved headgear on the rate of head and face injuries in high school girls' lacrosse. METHODS: This was a prospective cohort study. The study group included three JV and five varsity girls' lacrosse teams, as well as their game opponents, who were mandated to wear headgear for all practice and game events over the course of the 2016-2017 and 2017-2018 lacrosse seasons. Certified athletic trainers assessed and documented all injuries that occurred as a result of participation on the lacrosse teams and athlete exposures were estimated based on the number of team practice and game events. Injury rates were compared with those from the High School RIO (Reporting Information Online) injury data reports from the 2008-2009 to 2015-2016 lacrosse seasons as well as an external publication based on RIO data that provided concussion injury rates. RESULTS: Over the study period, 17 total injuries were reported during 22397 athlete exposures (AEs), for an injury rate of 0.76 injuries per 1000 AEs. Two total head/face injuries (2 concussions) were reported during the study for both a head/face and concussion rate of 0.09 per 1000 AEs. There was a significant decrease in injury rates for total injuries (RR 0.4927; 95% Confidence Interval [CI], 0.3037-0.7995; P-value 0.004) and head/face injuries (RR 0.2232; 95% CI, 0.2232-0.055; p-value 0.016) when comparing this data to the HS RIO study reports. When compared to the concussion data provided by the external RIO publication, there was a lower injury rate that was not found to be significant (RR 0.26; 95% CI, 0.0630 -1.033; p-value: 0.03879). DISCUSSION AND CONCLUSION: Headgear use did not increase the injury rate for the head/face when compared to data before the optional headgear use rule. This may help to dispel fears over an injury rate that would increase due to more aggressive play or less cautious officiating.